Analisis Pengarug Aglomerasi Industri, Tingkat Partisipasi Angkatan Kerja (TPAK) dan Nilai Output Industri terhadap Laju Pertumbuhan Ekonomi di Sumatera Utara - Novita Tanjung; Fauzi Arif Lubis; Juliana Nasution (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to determine whether the Industrial Agglomeration, Labor Force Participation Rate (TPAK) and Output Value affect Economic Growth in North Sumatra. This research is a quantitative study using secondary data. The number of samples for this study is time series data for 2016-2020 and interpolated to 59. The data was processed through SPSS Program version 22 with technical data analysis using multiple linear regression analysis. The results of the study proved that agglomeration, TPAK and output value have a significant effect on economic growth in North Sumatra. Based on the results of the first hypothesis test, a significant value of Agglomeration of 0.001(sig<0.05) with a calculated t value of 1.610 < 2.003241(t hitunf < t table is known). The second hypothesis test showed a significant value of TPAK 0.000(sig < 0.05) with a calculated t value of 1.494 < 2.003241(t count< t table), and based on the third hypothesis test, it was known that the significant value of industrial output 0.000(sig < 0.05) with a calculated t value of 0.418 < 2.003241(t count < t table). Based on the conclusion that it can be known the most dominant free variable that affects bound variables is the Tpak variable which has a coefficient value of β 2.071 compared to other variables. Then from the results of the F test proved that the agglomeration of industry, TPAK and output values simultaneously or together had a significant effect on the Economic Growth Rate in North Sumatra which was indicated by the significant value of F < α (0.000<0.05). Keywords: industrial agglomeration, labor force participation rate, industrial output value, economic growth.